The basic principles of chimeric antigen receptor (CAR) design - Sadelain, Michel (2013)
CARs are recombinant receptors that provide both antigen-binding and T cell activating functions. A multitude of CARs has been reported over the past decade, targeting an array of cell surface tumor antigens. Their biological functions have dramatically changed following the introduction of tri-partite receptors comprising a costimulatory domain, termed second generation CARs. These have recently demonstrated clinical benefit in patients treated with CD19-targeted autologous T cells. CARs may be combined with costimulatory ligands, chimeric costimulatory receptors or cytokines to further enhance T cell potency, specificity and safety. CARs represent a new class of drugs with exciting potential for cancer immunotherapy.